EFFORTS TO IMPROVE FINE MOTOR SKILLS THROUGH CUTTING ACTIVITIES USING PATTERNS IN GROUP A AT PURWAKARTA NATURE KINDERGARTEN - Munawaroh, Latifah; Syahidin, Samin; Jannah, Miftachul (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to develop and improve fine motor skills through cutting activities in early childhood in Group A of Purwakarta Nature Kindergarten. Fine motor skills are an important aspect of early childhood development because they support writing, drawing, and daily activities that require hand-eye coordination. The research method used was Classroom Action Research (CAR), implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of this study were 15 children in Group A of Purwakarta Nature Kindergarten. This study was conducted in the first semester of the 2025/2026 academic year. Data collection techniques used in this study were observation and assessment of pattern cutting skills. The research results indicate an improvement in children's fine motor skills in each cycle. Children are increasingly able to hold scissors correctly, follow patterns more neatly, and demonstrate perseverance and independence. It can be concluded that cutting activities using patterns are very effective in developing or improving fine motor skills in Group A children at Purwakarta Nature Kindergarten in the first semester, by 30.5%.